Microcirculation Revisited - From Molecules to Clinical Practice 2016
DOI: 10.5772/64529
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Regeneration by Endothelial Progenitor Cells in Health and Diseases

Abstract: Human endothelial progenitor cells (hEPCs) are adult stem cells, located in the bone marrow and peripheral blood. These cells can be differentiated into mature endothelial cells, which are involved in processes of angiogenesis and vessel regeneration. Different phenotypes and subtypes of endothelial progenitor cells (EPCs), such as early and late EPCs, have been described according to their functionality. Thus, it has been shown that early EPCs release cytokines that promote tissue regeneration and neovasculog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 150 publications
(170 reference statements)
0
3
0
Order By: Relevance
“…(8) In principle, the mechanisms of EPCs in neovascularization involve mobilization, homing, and differentiation into endothelial cells. (11,(14)(15)(16) During ischemia or vascular injury, VEGF and stromal cellderived factor 1 (SDF-1) are upregulated and released in circulation. These substances activate endothelial nitric oxide synthase (eNOS) to produce nitric oxide (NO), followed by activation of matrix metalloproteinase-9 (MMP9).…”
Section: Basic Of Epcsmentioning
confidence: 99%
“…(8) In principle, the mechanisms of EPCs in neovascularization involve mobilization, homing, and differentiation into endothelial cells. (11,(14)(15)(16) During ischemia or vascular injury, VEGF and stromal cellderived factor 1 (SDF-1) are upregulated and released in circulation. These substances activate endothelial nitric oxide synthase (eNOS) to produce nitric oxide (NO), followed by activation of matrix metalloproteinase-9 (MMP9).…”
Section: Basic Of Epcsmentioning
confidence: 99%
“…Although they share some endothelial phenotypes, they possess different morphologies, proliferation rates, and survival features along with different gene expression profiles (Balbarini & Di Stefano, 2008). It has been also shown that early EPCs release cytokines promoting tissue regeneration and neovasculogenesis, whereas late EPCs contribute to the formation of blood vessels and stimulate tube formation (Nova-Lamperti et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…E2, estradiol; EPCs, endothelial progenitor cells; ECs, endothelial cells; NO, nitric oxide; VEGF, vascular endothelial growth factor; c-kit, type III receptor tyrosine kinase; ERα, estrogen receptor α. This cartoon was inspired by Nova-Lamperti et al, 2016[74].…”
mentioning
confidence: 99%